1980
DOI: 10.1063/1.91491
|View full text |Cite
|
Sign up to set email alerts
|

High photocurrent polycrystalline thin-film CdS/CuInSe2 solar cella

Abstract: A polycrystalline thin-film Cds/CuInSe2 heterojunction solar cell with an efficiency of 5.7% has been prepared using a simultaneous elemental evaporation technique to deposit the CuInSe2 film. The cell–s short(-circuit current of 31 mA/cm2 under 100 mW/cm2 is the highest ever reported for a 1-cm2 cell. Heat treatments have been found to improve cell efficiency and to also change the cell I-V and C-V characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(25 citation statements)
references
References 1 publication
2
22
0
1
Order By: Relevance
“…A typical CuInSe 2 (CIS) or Cu(In,Ga)Se 2 (CIGS) based solar cell comprises a glass/Mo/(CIS/CIGS)/CdS/i-ZnO/ZnO heterojunction with the molybdenum film being used as a back contact layer [1]. The reason is partially historic and partly scientific [2].…”
Section: Introductionmentioning
confidence: 99%
“…A typical CuInSe 2 (CIS) or Cu(In,Ga)Se 2 (CIGS) based solar cell comprises a glass/Mo/(CIS/CIGS)/CdS/i-ZnO/ZnO heterojunction with the molybdenum film being used as a back contact layer [1]. The reason is partially historic and partly scientific [2].…”
Section: Introductionmentioning
confidence: 99%
“…[40] Boeing Corporation developed the first efficient (10 %) thin-film devices in the early 1980s using a vacuum-based three-source coevaporation process. [41] With some modifications (multistage rather than a two-stage method) it is still the record-performance process used today. [4] Evaporation approaches facilitate achieving high efficiencies because of the possibility to control elemental fluxes during high-temperature reactions.…”
Section: Chalcopyrite-based Absorber Materials and Devicesmentioning
confidence: 99%
“…The biggest, confirmed today for SC based on CdS/CdTe, is 16,5% efficiency in which CdS film was chemically deposited in bath (Green at al., 2011). Entering highly resistive CdS film in p-CuInSe 2 /CdS/n-CdS solar cell structure deemed necessary step towards improving of the solar cells stability (Mickelsen & Chen, 1980). Performed theoretical calculations (Rothwarf, 1982) showed that the thickness of CBD CdS films should be as small as possible to increase efficiency of solar cells with its use.…”
Section: Peculiarities Of Chemical Bath Deposition (Cbd)mentioning
confidence: 99%